Is kidney donation deleterious? Evaluation of renal function in postnephrectomy living donors (Colombia Medica, 1992)
Postnephrectomy renal function was studied in 38 living-related kidney donors. Serum creatinine values were 92.02 +- 0.64 umol/l, i.e., 22,7% higher than pre nephrectomy levels. Creatinine clearance was 95.5% of donation figures and 91.7% of values in the control group. Albuminuria was found in 4 patients (ranges: 40-70mg 24h). Hypertension was seen in 1 (2.6%) patient. According to these findings, unilateral nephrectomy in donors was not associated with significant risks for the functions of the remaining kidney.